Hierarchical planning and information sharing techniques in supply chain management - Taghipour, Atour, 1974- (Advances in logistics, operations, and management science (ALOMS) book series., 2019)
"This book addresses the coordination of operations planning of supply chains involves simplifying complex decision problems into a hierarchy of mutually inter-dependent decision problems. It also provides insights and support executives concerned with the management of expertise, knowledge, information and organizational development in different types of work communities and environments"--